Effect of Fe-Ni Substitution in FeNiSiB Soft Magnetic Alloys Produced by Melt Spinning - Kılıçaslan, Muhammed Fatih; Yılmaz, Yasin; Akgül, Bekir; Karataş, Hakan; Vurdu, Can Doğan (Walter de Gruyter GmbH, 2021)
Abstract Alloys of FeNiSiB soft magnetic materials containing variable Fe and Ni contents (wt.%) have been produced by melt spinning method, a kind of rapid solidification technique. The magnetic and structural properties of FeNiSiB alloys with soft magnetic properties were investigated by increasing the Fe ratio. X-ray diffraction analysis and SEM images shows that the produced alloy ribbons generally have an amorphous structure, together with also partially nanocrystalline regions. It was observed that the structure became much more amorphous together with increasing Fe content in the composition. Among the alloy ribbons, the highest saturation magnetization was obtained as 0.6 emu/g in the specimen with 50 wt.% Fe. In addition, the highest Curie temperature was observed in the sample containing 46 wt.% Fe.